Factors Contributing to Increased Patient Wait Times in Selected Wound Care Patients: A Retrospective Study (International Journal of Studies in Nursing, 2018)
Background: ‘Waiting’ can be frustrating for anyone especially when it comes to healthcare. The Institute of Medicine advocates changes to improve the quality of the health care delivery system in the United States. Purpose: The purpose of this retrospective study was to determine the factors contributing to increased patient wait times in selected wound care patients. The question guiding this project is-in selected wound care patients who received treatment between September1-December 31, 2013; are factors contributing to prolonged wait times related to treatment-related diagnosis, providers, and clinicians? Method: After institutional review board approval, retrospective charts review was conducted. 300 charts were randomly selected from the electronic health record (EHR) database at a local hospital wound care clinic. 120 charts met the inclusive criteria and were analyzed using ANOVA and SPSS version 22. The Deming cycle for quality improvement was adopted as the framework for practice review and changes. Result: Among all the factors examined, Treatment diagnosis accounted for 4% of the variance (p = 0.416); Providers 1% (p = 0.208); and Clinicians 8% (p = 0.195). Though clinicians had the highest variance, it was not a significant factor for patient wait times. The Deming cycle helps to prioritize and improve communication by creating a chart for effective patient flow through the clinic to reduce wait time. Conclusion: Correcting and improving wait times has the potential for increasing timely access and patient satisfaction. Clinicians and providers are not significant factors contributing to wait times. Wait time should be given priority and be regularly reviewed as part of the quality improvement plan within any organization.